Xavier Frías Conde in the collection "O Roibén", the relevant poetical contribution of one of the founders of the Grupo Bilbao - Luna, Luis (Madrygal. Revista de Estudios Gallegos, 2012)
Xavier Frías Conde played an important role in the consolidation of the so-called Grupo Bilbao, one of the most active writers’ group outside Galicia. As one of the founders of the Group, he proposed a set of literary tools to facilitate the group's literary production. One of them is the foundation of a notebook collection, O Roibén, which happens to be crucial to understand Galician literary creation in Madrid. Its issues, both collectively and individually, are a must to understand the creative process of this group.
Keywords: Contemporary Galician Poetry; Xavier Frías Conde; Grupo Bilbao; Poetry Collection O Roibén.